SMES TAX AWARE: Analysis of the Obligation to Pay Taxes, Knowledge and Tax Incentives - Ginting, Irwan (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2023)
Taxes are still perceived negatively by the public, because paying taxes means losing some of the profits, especially in small and medium scale businesses, the obligation to pay taxes is considered a burden. Therefore, there needs to be a revolution in the application of benefits-based taxes, so that awareness of paying taxes is built. This research was conducted to look at the causal relationship regarding compliance with paying taxes among small and medium enterprises in Karo district, North Sumatra. To test this, quantitative principles based on numerical data are used, so that the research results are easier to explain. The research subjects were 100 small and medium business actors, which were taken using a simple random technique. Data analysis was performed using linear regression statistical methods with partial, simultaneous and determinant tests. The results of the study explain that compliance with paying taxes is caused by many factors. However, in real conditions on the ground, compliance with paying taxes is still influenced by the rules on the obligation to pay taxes. This is confirmed by research findings which show that increased knowledge of the obligations of preparing financial reports can increase awareness of paying taxes. Because in the financial statements it is recorded and calculated how many tax obligations must be paid.